2021
DOI: 10.1111/ced.14785
|View full text |Cite
|
Sign up to set email alerts
|

Limited utility of plasma elafin as a biomarker for skin graft‐versus‐host disease following allogeneic stem cell transplantation

Abstract: Background. Acute cutaneous graft-versus-host disease (acGVHD) following haematopoietic stem cell transplant (HSCT) is common but difficult to distinguish from other causes of rash. Plasma elafin has been proposed as a diagnostic and prognostic biomarker of skin GVHD. Aim. To evaluate the role of plasma elafin as a biomarker in acGVHD in an Indian population. Methods. Plasma elafin was evaluated in a prospective study of HSCT recipients, conducted over 2 years, taking measurements at baseline and at onset of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…It has been demonstrated that elevated plasma level of PI3 correlates with cutaneous aGvHD and disease severity [19], and these initial findings have been confirmed by others as well [20]. Nevertheless, PI3 is inferior to REG3A as a prognostic marker when determining non-relapse mortality or over-all survival [21], and it has been suggested that PI3 may be inappropriate for the differential diagnosis of skin damage induced by cutaneous aGvHD [22]. Finally, the intestinal-type fatty acid-binding protein (FABP2) is another gut-restricted antimicrobial protein the dysregulation of which has been also reported in the blood in aGvHD [23,24].…”
Section: Introductionmentioning
confidence: 84%
“…It has been demonstrated that elevated plasma level of PI3 correlates with cutaneous aGvHD and disease severity [19], and these initial findings have been confirmed by others as well [20]. Nevertheless, PI3 is inferior to REG3A as a prognostic marker when determining non-relapse mortality or over-all survival [21], and it has been suggested that PI3 may be inappropriate for the differential diagnosis of skin damage induced by cutaneous aGvHD [22]. Finally, the intestinal-type fatty acid-binding protein (FABP2) is another gut-restricted antimicrobial protein the dysregulation of which has been also reported in the blood in aGvHD [23,24].…”
Section: Introductionmentioning
confidence: 84%
“…Moreover, Brüggen et al suggested an association between ela n expression in the skin and poor prognosis for patients with cutaneous GVHD (18). On the other hand, recent studies found no difference in ela n concentration between clinical stages of skin disease and no correlation with the 6month nonrelapse mortality as well as showed that ela n does not help to distinguish between GVHD skin lesions and other causes of rash following HSCT (7,11). In our study, patients suffering from GvHD presented the highest concentration levels of all analyzed groups of diseases, although, in contrast to previous reports, these were patients who quali ed as ccGvHD.…”
Section: Discussionmentioning
confidence: 99%
“…According to the subset classi cation of SSc, there were 35 patients with diffuse cutaneous (dcSSc) and 3 with limited cutaneous form (lSSc) based on the extent of their skin involvement. The patients' history included evaluation of skin involvement using modi ed Rodnan skin thickness score (11), lung and renal involvement.…”
Section: Methodsmentioning
confidence: 99%
“…Also, low tissue amphiregulin expression on immunohistochemistry has been reported in 74% of patients with acute gut GVHD and might aid in diagnosis without classic apoptotic changes ( 58 ). Similarly, tissue, and not plasma, elafin on immunohistochemistry can aid in diagnosing acute GVHD involving the skin ( 59 , 60 ).…”
Section: Biomarkers For Acute Gvhdmentioning
confidence: 99%
“…Elafin was initially discovered to be associated with skin GVHD ( 48 ). However, its utility appears very limited owing to the lack of reproducibility ( 60 ). The inclusion of elafin to REG3α and ST2 was also shown to be of little value in improving the accuracy of assessing HSCT outcomes ( 109 ).…”
Section: Single Biomarker Vs Panelmentioning
confidence: 99%